(untitled) (Лучшие интеллектуальные исследования, 2025)
The article "Integrating Critical Thinking into the English Curriculum: A Practical Guide" explores the significance of fostering critical thinking skills within English language education. It outlines effective strategies for educators to incorporate critical thinking into their teaching practices, enhancing students’ analytical abilities, creativity, and engagement with texts. The authors provide a framework that includes specific activities, discussion prompts, and assessment methods designed to cultivate a critical mindset among learners. By emphasizing the interconnectedness of critical thinking and language skills, the article serves as a valuable resource for teachers aiming to create a more dynamic and intellectually stimulating English curriculum.